Evaluation of a rapid identification method for Neisseria spp. - Germer, J J (1985)
A comparison was made of carbohydrate degradation reactions of Neisseria gonorrhoeae, Neisseria meningitidis, Neisseria lactamica, Neisseria mucosa, Neisseria sicca, Neisseria subflava, and Branhamella catarrhalis in a rapid (0.5- to 1-h) identification micromethod (RIM-N Kit; Austin Biological Laboratories, Inc., Austin, Tex.) and in a serum-free agar slanted medium (72 h). Reactions after 1 h in the RIM-N system agreed completely with those after 72 h in the conventional system.